Morphological and molecular characterizations of psychrophilic fungus Geomyces destructans from New York bats with White Nose Syndrome (WNS). - Vishnu Chaturvedi (Public Library of Science (PLoS), 2010)
Background Massive die-offs of little brown bats (Myotis lucifugus) have been occurring since 2006 in hibernation sites around Albany, New York, and this problem has spread to other States in the Northeastern United States. White cottony fungal growth is seen on the snouts of affected animals, a prominent sign of White Nose Syndrome (WNS). A previous report described the involvement of the fungus Geomyces destructans in WNS, but an identical fungus was recently isolated in France from a bat that was evidently healthy. The fungus has been recovered sparsely despite plentiful availability of afflicted animals. Methodology/principal findings We have investigated 100 bat and environmental samples from eight affected sites in 2008. Our findings provide strong evidence for an etiologic role of G. destructans in bat WNS. (i) Direct smears from bat snouts, Periodic Acid Schiff-stained tissue sections from infected tissues, and scanning electron micrographs of bat tissues all showed fungal structures similar to those of G. destructans. (ii) G. destructans DNA was directly amplified from infected bat tissues, (iii) Isolations of G. destructans in cultures from infected bat tissues showed 100% DNA match with the fungus present in positive tissue samples. (iv) RAPD patterns for all G. destructans cultures isolated from two sites were indistinguishable. (v) The fungal isolates showed psychrophilic growth. (vi) We identified in vitro proteolytic activities suggestive of known fungal pathogenic traits in G. destructans. Conclusions/significance Further studies are needed to understand whether G. destructans WNS is a symptom or a trigger for bat mass mortality. The availability of well-characterized G. destructans strains should promote an understanding of bat-fungus relationships, and should aid in the screening of biological and chemical control agents.